Global Variability of Density Contrast Across the 660‐km Discontinuity. Issue 4 (16th February 2023) - Wang, Jingchuan; Gu, Yu Jeffrey; Schmerr, Nicholas
Abstract: This study investigates lateral variations in density contrast across the 660‐km discontinuity, which is critical for understanding mantle convection and composition. We produce a global map of density jump, with values ranging from 3.8% to 9.3%, at the mineralogical phase boundary by applying inversions of amplitude variations with offset to underside S reflections. Our observations reveal a global average velocity jump of 4.1% and a density jump of 5.3%, favoring a pyrolitic bulk composition. Near major subduction zones, most notably the western Pacific and South America, we identify reduced density jumps in regions of depressed 660‐km discontinuity, consistent with basalt fractions greater than 30% in a mechanically mixed mantle. The causal association between density jump and compositional changes is further supported by a moderate correlation between lateral variations in density jump and those of water content anomalies. Plain Language Summary: The Earth's mantle is subdivided by a solid‐to‐solid phase change of the mineral olivine near 660 km depth with sharp increases in seismic velocity and density. The physical properties of this phase boundary directly impact our understanding of mass and heat transfer from the Earth's deep mantle to the surface. In this study, we analyze an up‐to‐date data set of bottom‐side reflections, also known as SS precursors, to estimate global variations in density jump at the base of the upper mantle. We find reduced density jumps near regions where oceanic lithospheres are being recycled into the deep mantle. Lateral variations in density contrast show a moderate correlation with the estimated water content in the mantle transition zone (400–700 km depth). Key Points: We use an amplitude‐versus‐offset inversion of SS precursors to constrain density properties of the 660‐km discontinuity We map global variations in density jump across the 660‐km discontinuity Lateral variations in density jump reflect compositional variations and are correlated with transition zone water distribution